Exhaust manifold thermal and flow analysis - Duman, İpek (My University, 2016)
Nowadays, reducing the fuel consumption, increasing the performance and efficiency of engine are the significant customer demands for the automotive industry. To meet the customer expectations and overcome this engineering challenge, new generation diesel engines are developed by using direct injection technology (common rail), turbocharger application considering the downsizing trend. Due to the downsizing, turbocharging, injection technology development and obligation of compliying with the emission regulations, engine out exhaust gas temperature reaches over 800 °C for diesel engine. Through the engine operating condition, exhaust manifold is exposed high thermal stresses due to the elevated exhaust gas temperature. Exhaust manifold metal surface temperature increase very quickly and extreme transient temperature gradient can occur. Thermomechanical fatigue cracks are observed as a result of the cyclic manner thermal loading. To come up with a robust and durable engine exhaust manifold design, it is required well developed CAE methodology to predict accurate transient temperature distribution on exhaust manifold. Then the predicted metal temperature is used to carry out the thermo-structure durability analysis evaluating the design of exhaust manifold. In this study, investigated the feasibility of three different CAE approaches called conjugate heat transfer analysis, sequential coupling and co-simulation to assess the temperature field of heavy duty diesel engine exhaust manifold.Apart from the numerical calculation, performed thermal camera measurement called thermal survey on the Ecotorq 12.7 L heavy duty diesel engine at Gölcük dynamometer laboratory to validate the CAE results.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Keywords: Ağır ticari araç motoru; Egzoz manifoldu; Sıcaklık dağılımı; Hesaplamalı akışkanlar dinamiği; Bileşik ısı transferi; Termal kamera